Unlocking Female Fertility with a Specific Reproductive Exercise Program: Protocol of a Randomized Controlled Clinical Trail - Barbara Petra Kovács; Júlia Balog; Barbara Sebők; Márton Keszthelyi; Szabolcs Várbíró (Life)
According to World Health Organization (WHO) data, 16% of people are affected by infertility across the globe. One underlying factor is the age-related decline of ovarian reserve (DOR), which can lead to a higher chance of infertility and has no widely accepted treatment currently. Specific supplements and moderate exercise have been shown to improve fertility; however, there is no consensus to date on the type of exercise providing the best results. Our goal is to develop a novel exercise program combined with natural supplements for the improvement of fertility. We also propose a single-centered, randomized, open-label clinical trial using our newly developed exercise in the intervention group, compared to walking and no exercise in the other groups, to investigate the benefits of this exercise program in the future. In this study, we developed a structured, novel combination of exercises focusing on the pelvic and ovarian regions, core strengthening and improvement of blood circulation in this region. The 70 min full body “reproductive gymnastics”, includes strengthening, stretching, and relaxation exercises combined with yoga-inspired moves and diaphragmatic breathing with meditation elements to activate the parasympathetic pathway and stress relief. We believe we can improve fertility through the combination of natural supplements and our targeted, moderate physiotherapy program in women with DOR.